THE EFFECT OF INTRALINGUAL SUBTITLED AND NON-SUBTITLED DOCUMENTARY VIDEOS ON VOCABULARY RETENTION FOR ELEVENTH GRADE STUDENTS (RETAIN, 2017)
THE EFFECT OF INTRALINGUAL SUBTITLED AND NON-SUBTITLED DOCUMENTARY VIDEOS ON VOCABULARY RETENTION FOR ELEVENTH GRADE STUDENTS Inarotul Iklimaini English Education Department, Faculty of Languages and Arts, State University of Surabaya ilmaiklimaini@gmail.com Abstrak Kosakata adalah salah satu komponen bahasa Inggris yang mendukung kemampuan bahasa Inggris. Sekarang ini, pengajaran kosa kata bahasa Inggris dengan menggunakan media telah menarik di dalam penelitian. Penelitian ini mencoba menganalisis pengaruh video intralingual terjemahan dokumenter dan video tanpa terjemahan sebagai media pengajaran kosakata untuk mengetahui apakah bisa meningkatkan retensi kosa kata siswa di kelas SMA. Sejalan dengan reserach ini, digunakan desain kuantitatif. Penelitian ini juga bertujuan untuk mengetahui bagaimana tanggapan siswa terhadap pengamatan video. Penelitian ini menyelidiki siswa kelas XI (N = 70) belajar kosa kata bahasa Inggris dengan video dokumenter subtitle dan nonsubtitled. Tersedia siswa kelompok kontrol dan siswa kelompok eksperimental. Untuk mengetahui efek media ini, uji kosa kata diberikan sebagai uji tes awal segera, uji tes akhir, uji tes akhir tertunda1, dan uji tes akhir tertunda2. Hasil data menunjukkan bahwa efek video subjudul intralingual dan video non-subjudul, siswa yang mendapat perawatan dengan menggunakan video intralingual terjemahan ditingkatkan untuk mengingat dan mengenali retensi kosa kata dalam jangka waktu pendek dan waktu yang lama. Jelas, kesimpulan tanggapan siswa terhadap menonton video, kelompok eksperimen setuju bahwa video terjemahan intrektif adalah media yang efektif untuk mempelajari retensi kosa kata, dan memiliki respon positif daripada siswa kelompok kontrol. Oleh karena itu, guru harus lebih kreatif dan terampil mengajar kosa kata terhadap karena bisa memberi dampak kepada siswa terhadap proses belajar mengajar. Kata Kunci: Terjemahan, Tanpa Terjemahan, Video Dokumenter, Retensi Kosakata ABSTRACT Vocabulary is one of English components which supports English skill. Nowadays, teaching English vocabulary by using media has been interesting in research. This study tried to analyze the effect of subtitled and non-subtitled documentary video as media on teaching vocabulary to know whether it could incerase students’ vocabulary retention in Senior High School classes. In line with this reserach, it was used quantitative design. This study also aims to find out to how the students’ response towards watching the video.This study was investigated eleventh grade students (N=70) learn English vocabulary with subtitled and nonsubtitled documentary video. There were control group students , and experimental group students. To know the effect of this media, the vocabulary test were administered as immediate pretest, immediate posttest, delayed posttest1, and delayed posttest2. The result of the data show that the effect of intralingual subtitled videos and non-subtitled video is the students who are got the treatment by using intralingual subtitled videos are improved to recall and recognize the vocabulary retention in short-time period and long-time perod. Obviously, inconclusion of students’ response toward watching the video, the experimental group students are agree that intralingual subtitled video is effective media for learning vocabulary retention, and have possitive response rather than control group students. Therefore, teacher should be more creative to teach the students vocabulary skill because it can give the students impact for teaching and learning process. Keywords: Subtitled, Non-Subtitled, Documentary Video, Vocabulary Retention